Suppression of argatroban-induced endogenous thrombolysis by PKSI-527, and antibodies to TPA and UPA, evaluated in a rat arterial thrombolysis model - Hashimoto, Masaru; Oiwa, Kazuhiro; Matsuo, Osamu; Ueshima, Shigeru; Okada, Kiyotaka; Okada, Yoshio; Okamoto, Shosuke; Giddings, John C.; Yamamoto, Junichiro (Thrombosis and Haemostasis, 2003)
We have previously confirmed, using a rat mesenteric arteriole thrombolysis model, that thrombin inhibition induces endogenous thrombolysis in vivo. In addition, we have shown that thrombin-activatable fibrinolysis inhibitor (TAFI) plays a role in the down regulation of endogenous thrombolysis. However, the mechanism of endogenous thrombolysis or spontaneous plasmin generation in vivo remains unclear.It has been shown in an in vitro system that plasma kallikrein activates pro-urokinase (pro uPA) and/or plasminogen, resulting in plasmin generation. These findings suggest that spontaneous fibrinolysis might be mediated by tPA and plasma kallikrein-dependent uPA. The aim of the present study was to examine whether these mechanisms play a dominant role in endogenous thrombolysis in vivo, using our rat mesenteric arterial thrombolysis model.Argatroban infusion enhanced endogenous thrombolysis. PKSI-527, anti uPA and anti tPA IgGs suppressed argatroban-induced thrombolysis. Also, the antibody IgG preparations suppressed endogenous thrombolysis in the absence of argatroban. In the presence of PKSI-527, anti tPA IgG was more effective than anti uPA IgG in suppressing argatroban-induced thrombolysis. The results suggested that both tPA and plasma kallikrein-mediated uPA activation and tPA release contribute to endogenous fibrinolytic or thrombolytic mechanisms.
Keywords: Endogenous thrombolysis; plasma kallikrein; plasminogen activator; TAFI; animal model